Community Knowledge and Self-Awareness on Risk Factors for Chronic Kidney Disease (CKD) in Bali, Indonesia - Ni Wayan Kesari Dharmapatni; Ni Made Manik Elisa Putri (Babali Publisher, 2023)
Introduction: In Indonesia, CKD is among the top 10 most prevalent diseases, with the prevalence increasing sharply from 2013 to 2018. Therefore, prevention should focus on reducing risk factors for people who have not yet suffered from CKD. Based on the above, researchers are interested in examining the relationship between knowledge and community self-awareness of CKD risk factors in Bali. Methods: This study used descriptive analysis with a cross-sectional approach. The population in the study was all Balinese people, with a sample size of 209 respondents who met the inclusion criteria. The research was conducted by means of an online survey consisting of demographic data, Self-Awareness Questionnaire and CKD Knowledge Questionnaire through Google Forms. The collected data were analyzed with univariate and bivariate analyses. Results: Most of the respondents were from adolescence to early adulthood (17–35 years old)—as many as 78.2%, dominated by women (64.8%). Judging from the level of knowledge, more than half of the respondents fell into the sufficient category, namely 67%. While the level of community self-awareness tends to be high, with a result of 45%, Thus, there was a significant relationship between knowledge and self-awareness of the Balinese community towards CKD risk factors (p<0.01). Conclusion: Balinese people have a good level of knowledge and awareness of CKD risk factors. However, preventive measures are still needed to prevent an increase in these cases. It is hoped that health services would continue to provide information.